Management of submandibular abscess with candidiasis complications - Iip Berliananda; Benny Kurnia (School of Medicine, Universitas Syiah Kuala, 2023)
Submandibular space is part of the deep neck fascial spaces, bordered by the oral mucosa of the mouth floor on the above and the superﬁcial layer on the deep cervical fascia on the bottom, as it extends from the mandible to hyoid bone. Submandibular space frequently involves odontogenic infections, which can cause significant mortality and morbidity. Open surgical incision and drainage are the treatment of choice for submandibular space abscesses. This is a case report of a 47-years-old female with main complaint of mass on the right submandibular that she has experienced for 2 weeks. The mass release pus which is felt flow down the throat. Physical examination revealed a soft, tender mass of 55 mm x 20 mm diameter in the right submandibular region. Oral status of the patient revealed presence of oral candidiasis too. There was no complication of trismus, swallowing pain or paralysis of the lower lip. The patient’s temperature was 38.5⁰C. Laboratory examinations showed a raised white blood cell count and slightly decreased albumin level. Intraoral swelling and redness of gingiva on the right upper middle incisor were observed. The patient was successfully treated by abscess drainage, oral antibiotics and nystatin.